Religion, Migration and Identity Methodological and theological explorations - Frederiks, Martha; Nagy, Dorottya (Theology and Mission in World Christianity, 2016)
In Religion, Migration and Identity scholars from various disciplines explore issues related to identity and religion, that people - individually and communally -, encounter when affected by migration dynamics; the volume foregrounds methodology as its main concern. Readership: All interested in issues related to religion, migration and identity and anyone concerned with missiology, mission studies, world Christianity and the history of Christianity, theology or mission worldwide.